The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/aln.0000000000001056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Power and Development of Ventilator-induced Lung Injury

Abstract: Background The ventilator works mechanically on the lung parenchyma. The authors set out to obtain the proof of concept that ventilator-induced lung injury (VILI) depends on the mechanical power applied to the lung. Methods Mechanical power was defined as the function of transpulmonary pressure, tidal volume (TV), and respiratory rate. Three piglets were ventilated with a mechanical power known to be lethal (TV, 38 ml/kg; pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
316
4
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 343 publications
(362 citation statements)
references
References 32 publications
13
316
4
13
Order By: Relevance
“…Indeed, the effects of respiratory rate on VILI have been described in experimental animals (27,28). In particular, when we applied a strain greater than 2, which invariably leads to death when delivered at a rate of 15 bpm, we found a lack of injurious effect if delivered at 3 or 6 bpm (29). The relevance of respiratory rate underlines another possible scenario: indeed, in analogy with materials fatigue, it may be possible that damage occurs only after a given number of stress and strain cycles have been delivered and generated into the lung (i.e., VILI below the stress at rupture requires time).…”
Section: Respiratory Ratementioning
confidence: 54%
“…Indeed, the effects of respiratory rate on VILI have been described in experimental animals (27,28). In particular, when we applied a strain greater than 2, which invariably leads to death when delivered at a rate of 15 bpm, we found a lack of injurious effect if delivered at 3 or 6 bpm (29). The relevance of respiratory rate underlines another possible scenario: indeed, in analogy with materials fatigue, it may be possible that damage occurs only after a given number of stress and strain cycles have been delivered and generated into the lung (i.e., VILI below the stress at rupture requires time).…”
Section: Respiratory Ratementioning
confidence: 54%
“…Nevertheless, only a single respiratory cycle is measured when performing this calculation. To ascertain what happens over a longer period, power (energy multiplied by respiratory rate) is measured instead [22]. In this line, a recent study reported that VILI may develop if mechanical power exceeds 12 J/min.…”
mentioning
confidence: 98%
“…As a concept, the less you transfer energy to the injured lungs, the better it is. Even if this concept is mainly established in animal model (10), there are some arguments in a recent second analysis of the two randomized clinical trials PROSEVA and ACURASY of the impact of mechanical power on prognosis (11).…”
Section: Strengths Of the Studymentioning
confidence: 99%